The pathogenesis of amyloidosis in periodic disease: Some aspects - Z. T. Djndoyan (Klinicist)
Sufficient information indicating the implication of dysfunction of interleukins (IL-6 and IL-1 in particular) in the pathogenesis of amyloidosis in a number of autoinflammatory, rheumatic, and autoimmune diseases, including those in periodic disease (PD), has been recently accumulated. Its genetic defect – pirin mutation – gives rise to an alternative innate immune response (phagocytic cell activation) to secrete IL-1 by macrophages and to activate T-helper cells. This causes imbalance in the synthesis of proinflammatory (IL-6, IL-8, and TNF-α) and anti-inflammatory (IL-4, IL-10, and IL-1 receptor antagonist) cytokines. Moreover, the uncontrolled macrophage (monocyte) secretion of a great deal of IL-6 that together with IL-1 is a mediator of the synthesis of the serum amyloid fibril protein precursor SAA by hepatocytes, neutrophils, and fibroblasts plays one of the key roles in the pathogenesis of PD through amyloidosis. With this, IL-6 stimulates the inflammatory process, by enhancing the release of lysosomal enzymes, reactive oxygen species, and eicosanoids (prostaglandins, leukotrienes, thromboxane) from the polymorphic nuclear leukocytes, macrophages, endotheliocytes, and fibroblasts and by augmenting the chemotaxis of macrophages and neutrophils, and the degranulation of the latter, i.e. through its action on the effector cells of inflammation, and prepares the tissue basis for amyloid deposits in this fashion. Thus, the analysis of literary and own materials gives grounds to suggest that pirin mutation is a trigger of the synthesis of IL-1 and IL-6 in PD and their hypersecretion is an initial link of the synthesis of SAA.